Interpersonal Skills and Cooperative Learning in Psychology students from a private University in Guayaquil, 2023 - Paz Guerra, Stalyn Israel (2024)
The objective of this document is to propose a training plan based on the development of interpersonal skills with the aim of fostering cooperative learning among psychology students at a private university in Guayaquil in 2023. The research was conducted using a non-experimental design, which entailed observing and evaluating the variables or phenomena under investigation without any manipulation. The research findings indicate that inter-institutional alliances facilitate the expansion and enhancement of future psychologists' and professionals' competencies, offering them experiential learning opportunities in authentic work environments. The provision of internships in companies that offer training in this regard will be pivotal in complementing the academic training of students and better preparing them to address the issues they would encounter in professional practice. In this way, the university will not only fulfill its obligation to train competent professionals but will also become an agent of constructive social change.